A new archival hub at Wits University - (:unkn) unknown (My University, 2021)
For some years, the archives in South Africa have faced a series of unprecedented challenges that threaten the high quality of the documentation and the functioning of the centers that maintain them. The crises facing the State Archives reflect problems in the state more generally including inadequate strategic investment and lack of training, which jeopardise the potential renewal of archivists. At the same time, the wide array of political activities and social movements, the dynamics of civil society organizations and activism require more than ever to curate documentation and expand the archives’ capacities. To answer this paradox, a team working in two independent archives and a research center at Wits University is experimenting with a new “hub” to constitute an important center of independent archives in South Africa. Noor Nieftagodien, director of the Wits History Workshop - the research center that has played a role in the creation of the hub - and a member of the board of the South African Historical Archives, sheds light on the new enterprise.
Keywords: African Research